2017
DOI: 10.1016/j.ejps.2017.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage selective photodynamic therapy by meta-tetra(hydroxyphenyl)chlorin loaded polymeric micelles: A possible treatment for cardiovascular diseases

Abstract: Selective elimination of macrophages by photodynamic therapy (PDT) is a new and promising therapeutic modality for the reduction of atherosclerotic plaques. m-Tetra(hydroxyphenyl)chlorin (mTHPC, or Temoporfin) may be suitable as photosensitizer for this application, as it is currently used in the clinic for cancer PDT. In the present study, mTHPC was encapsulated in polymeric micelles based on benzyl-poly(ε-caprolactone)-b-methoxy poly(ethylene glycol) (Ben-PCL-mPEG) using a film hydration method, with loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 48 publications
9
59
0
Order By: Relevance
“…However, in a recent study, we showed a rapid release of this PS in the circulation after i.v. administration of the mTHPC-loaded PCL-PEG-based micelles [24]. The poor stability in the circulation is currently considered a limitation for micelles for successful clinical applications [24][25][26][27].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a recent study, we showed a rapid release of this PS in the circulation after i.v. administration of the mTHPC-loaded PCL-PEG-based micelles [24]. The poor stability in the circulation is currently considered a limitation for micelles for successful clinical applications [24][25][26][27].…”
mentioning
confidence: 99%
“…administration of the mTHPC-loaded PCL-PEG-based micelles [24]. The poor stability in the circulation is currently considered a limitation for micelles for successful clinical applications [24][25][26][27]. This instability is most likely due to a combination of extraction of the cargo from the micelles and micellar destabilization resulting from a large dilution volume upon injection or binding of drug-polymer chains to blood components (e.g., albumin, lipoproteins) [28].To overcome their inherent instability, physical interactions through π-π stacking have been investigated to enhance the stability of polymeric micelles.…”
mentioning
confidence: 99%
“…Among them, cardiovascular disease has being listed as a major cause of death and morbidity globally based on the status report of noncommunicable diseases in the world [1,[3][4][5][6][7]. Atherosclerosis, as a chronic inflammation with slow progressive buildup of lipids and macrophages within the arterial wall, is the primary contributor to myocardial infarctions and atherosclerotic plaque rupture [1,8]. In comparison with an open-heart surgery, angioplasty exhibits more benefits to patients and has been extensively employed to treat atherosclerosis by implanting an antithrombogenic agent-coated stent into the infected lesion in order to maintain an artery open after balloon angioplasty [3,9]; moreover, general anesthesia is unnecessary for patients.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, cardiovascular disease has being listed as a major cause of death and morbidity globally based on the status report of noncommunicable diseases in the world [1,[3][4][5][6][7]. Atherosclerosis, as a chronic inflammation with slow progressive buildup of lipids and macrophages within the arterial wall, is the primary contributor to myocardial infarctions and atherosclerotic plaque rupture [1,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation